Ratooning and perennial staple crops in Malawi. A review - (:unkn) unknown (My University, 2016)
AbstractThe management of staple crops as perennials is a historic legacy and a present-day strategy in some regions of Sub-Saharan Africa, yet perenniality is rarely an agronomic subject. Farmers in Malawi cut annual crops, such as pigeonpea and sorghum, to extend production for more than one growing season. Cassava, a perennial food crop, has a proven track record of abating hunger. Here we review ratooning, as well as the historic role of perennial staple crops in Malawi. Ratooning is a method of harvesting a crop which leaves the roots and the lower parts of the plant uncut to give the ratoon or the stubble crop. This review is completed with interviews with Malawian farmers. The major points follow. The management of staple crops as perennials is underserved by research. Indeed, we retrieved only 86 references on ratooning sorghum and pigeonpea. Of these, 9 % and 19 % respectively were from the African continent. The literature and interviews indicate that pigeonpea and sorghum have high productive potential when well managed in ratoon systems. Thirty-five percent of interviewee responses that supported ratooning mentioned saving seed. Other primary reasons to ratoon include stimulating regrowth (30 %) and saving labor (20 %). However, 31 % of responses that were against ratooning cited increased disease potential, as well as excessive vegetative regrowth (18 %).
Keywords: African Research